Karakteristik kimia, mikrob dan daya terima kukis sagu yang diperkaya Spirulina dan rumput laut: Sago cookies enriched with Spirulina and seaweed: chemical, microbial characteristics, and acceptability - Pari, Rizfi Faris; Setyaningsih, Iriani; Ramadhan, Wahyu; Tarman, Kustiariyah; Hardiningtyas, Safrina Dyah; Nurhayati, Tati; Desniar, Desniar; Uju, Uju; Aini, Khusnul (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Cookies are popular gluten-free snacks with low fiber and protein contents. Improving the quality of cookies by replacing wheat flour with sago flour and adding Spirulina and red seaweed Eucheuma cottonii reduced gluten levels, increased protein and fiber content, and enhanced appeal. The aim of this study was to determine the effect of adding E. cottonii on the quality of Spirulina cookies based on chemical, microbiological, and acceptability characteristics. Cookies were prepared by mixing ingredients using creaming (margarine and sugar), whisking (adding egg yolks), and all-in (adding sago flour, spirulina, and seaweed). Cookies were tested for proximate analysis, total plate count, water activity, bioactive compounds, nutritional adequacy score (NAS), and hedonic test analysis were conducted. The chemical compositions of the cookies increased by 4.32% and 0.56% in moisture and crude fiber contents, respectively. The microorganism content was within safe limits according to the Indonesian National Standard (